REFORMULASI PENGATURAN TINDAK PIDANA PENINDASAN (VERBAL BULLYING) YANG MENGAKIBATKAN KEMATIAN PADA ANAK - Dedek Putra; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Verbal bullying is this type of intimidation done verbally or with bad words with the aim of belittling, hurting, and also looking down on others. bullying verbal bullying is a form of